Klinkenberg-corrected and water permeability correlation for a sarawak carbonate field - Ahmad, I. (MDPI, 2021)
Klinkenberg-corrected permeability (kâ ) or water permeability (kw ) is an important input parameter for hydrocarbon reservoir simulation studies. The theoretical concept that a core sampleâs kâ is comparable to its kw is flawed and has to be verified, since experimental evidence indicates that kâ and kw are clearly different. Thus, a series of gas and water permeability measurements were conducted on eight carbonate core plug samples from Sarawak, Malaysia to develop a correlation between both permeability values. The new kâ vs. kw correlation clearly proved the differences between both permeability values for all samples. The findings were in agreement with FESEM-EDX and total suspended solids (TSS) analysis, which proved the migration of fines and clay particles that blocked the pore throats, thus reducing kw values. The new kâ vs. kw correlation was validated using four different samples from the PETRONS-2 well using its kâ values and comparing them with the respective measured kw values. The new correlation will reduce the amount of time and cost needed to obtain absolute liquid permeability values but may be further improved by conducting permeability measurements on more samples from the PETRONS field, which will improve the accuracy of hydrocarbon reservoir simulation of the PETRONS field. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.